Survival Analysis of Treatment Efficacy in Comparative Coronavirus Disease 2019 Studies. (14th October 2020) - McCaw, Zachary R; Tian, Lu; Kim, Dae Hyun; Localio, A Russell; Wei, Lee-Jen
Abstract: For survival analysis in comparative coronavirus disease 2019 trials, the routinely used hazard ratio may not provide a meaningful summary of the treatment effect. The mean survival time difference/ratio is an intuitive, assumption-free alternative. However, for short-term studies, landmark mortality rate differences/ratios are more clinically relevant and should be formally analyzed and reported.